2023
DOI: 10.1017/s1742170523000182
|View full text |Cite
|
Sign up to set email alerts
|

Cool-season cover crop effects on forage productivity and short-term soil health in a semi-arid environment

Anuoluwapo M. Ogunleye,
Akwasi Opoku,
Juan K.Q. Solomon
et al.

Abstract: There have been no systematic experiments conducted in Nevada's water-limited environment that examined the simultaneous benefits of soil health and feed value derived from cool-season cover cropping systems. The objective of this study was to determine the influence of different annual cool-season cover crop systems on above and belowground biomass production, plant tissue carbon and nitrogen, forage nutritive value (crude protein, acid, and neutral detergent fiber), relative feed value (RFV), and short-term … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Mukherjee and Lal (2015) measured the impacts of growing a pea/turnip CC for just one season in Central Ohio and only found a significant effect on soil pH and soil organic C at 0-10 cm. Over 2 years, winter CCs did not impact soil organic C, N, or microbial biomass indicators (0-15 cm) in a semiarid cropping system under irrigation in Nevada (Ogunleye et al, 2023). Measured effects on soil volumetric water content varied between years and treatments (Ogunleye et al, 2023).…”
Section: General Trends and Treatment Effectsmentioning
confidence: 92%
See 1 more Smart Citation
“…Mukherjee and Lal (2015) measured the impacts of growing a pea/turnip CC for just one season in Central Ohio and only found a significant effect on soil pH and soil organic C at 0-10 cm. Over 2 years, winter CCs did not impact soil organic C, N, or microbial biomass indicators (0-15 cm) in a semiarid cropping system under irrigation in Nevada (Ogunleye et al, 2023). Measured effects on soil volumetric water content varied between years and treatments (Ogunleye et al, 2023).…”
Section: General Trends and Treatment Effectsmentioning
confidence: 92%
“…Over 2 years, winter CCs did not impact soil organic C, N, or microbial biomass indicators (0-15 cm) in a semiarid cropping system under irrigation in Nevada (Ogunleye et al, 2023). Measured effects on soil volumetric water content varied between years and treatments (Ogunleye et al, 2023). In the semiarid agricultural region of the Canadian prairies, Wu et al (2024) found that CCs did not have a significant impact on soil health indicators across four sites, except for a reduction in spring soil nitrate.…”
Section: General Trends and Treatment Effectsmentioning
confidence: 96%
“…critical role in soil health and key soil processes related to nutrient release and uptake, soil aggregation, water dynamics, soil carbon storage, and nitrogen fixation (Blanco-Canqui et al, 2013;Blanco-Canqui et al, 2015;R. Ghimire et al, 2019;Magdoff et al, 2021;Ogunleye et al, 2023). Recent research in a semi-arid region of Texas reported that the high residue from winter wheat as a CC increased the microbial communities in sandy soils within 2 years for cotton cropping systems (Acosta-Martinez et al, 2023).…”
mentioning
confidence: 99%
“…Additionally, CC mixtures suppress weeds by rapidly producing canopy cover and allelochemicals (Koehler-Cole et al, 2020), control wind and water erosion, and prevent nutrient leaching. While several studies (Blanco-Canqui et al, 2015;Ogunleye et al, 2023) have reported cover crop diversity influence on physicochemical properties of the soil, there is a lack of information on the temporal dynamics of soil microbial communities following CC termination in arid and semiarid environments. Therefore, the primary objective of this study was to assess microbial community size and composition in response to diverse CCs and their mixtures in a winter wheat (Triticum aestivum L.)-sorghum (Sorghum bicolor L.…”
mentioning
confidence: 99%